Cu(i) based catalysts derived from bidentate ligands and studies on the effect of substituents for N-arylation of benzimidazoles and indoles. (6th November 2020) - Kumari, Sheela; Ratnam, Anand; Mawai, Kiran; Chaudhary, Virendra Kumar; Mohanty, Aurobinda; Ghosh, Kaushik
Abstract : Four Cu(i ) complexes [Cu(L 1–4 )(Cl)(PPh3 )] (C1–C4 ) were synthesized, characterized and crystal structure of C1 was determined. Complexes were utilized as catalysts for N -arylation reaction. Probable mechanism for N -arylation reaction was proposed. Abstract : A family of Cu(i ) complexes [Cu(L 1–4 )(Cl)(PPh3 )] (C1–C4 ) were synthesized from bidentate ligands L 1 –L 4 (where L 1 = ( E )-2-(2-benzylidene-1-phenylhydrazinyl)pyridine, L 2 = ( E )- N, N -dimethyl-4-((2-phenyl-2-(pyridin-2-yl)hydrazono)methyl)aniline, L 3 = ( E )-2-(2-(4-chlorobenzylidene)-1-phenylhydrazinyl)pyridine and L 4 = ( E )-2-(2-(4-nitrobenzylidene)-1-phenylhydrazinyl)pyridine) and characterized. The structure of complex C1 was authenticated by single-crystal X-ray diffraction. These complexes were utilised as catalysts for N -arylation of benzimidazoles and indoles. The effect of the substituents in the ligand frame of metal complexes were examined and the probable reaction pathway was scrutinized.